2020
DOI: 10.3389/fpls.2019.01755
|View full text |Cite
|
Sign up to set email alerts
|

Combining Simple Phenotyping and Photothermal Algorithm for the Prediction of Soybean Phenology: Application to a Range of Common Cultivars Grown in Europe

Abstract: Developing new cropping strategies (very early sowing, crop expansion at higher latitudes, double cropping) to improve soybean production in Europe under climate change needs a good prediction of phenology under different temperature and photoperiod conditions. For that purpose, a simple phenology algorithm (SPA) was developed and parameterized for 10 contrasting soybean cultivars (maturity group 000 to II). Two experiments were carried out at INRA Toulouse (France) for parameterization: 1) Phenological monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…There are studies to identify potent indigenous and commercial Bradyrhizobia inoculants suitable for European conditions (Zimmer et al, 2016;Yuan et al, 2020) and attempt to incorporate soybeans in the no-till cover-crop system (Halwani et al, 2019). However, very little is known about the potential of soybeans in higher latitudes (Lamichhane et al, 2020;Schoving et al, 2020). Soybean seeds contain high nutrients for feed and food use, and the crop establishes nitrogen-fixing symbiosis with Bradyrhizobia, fixing 68% and 119 kg ha −1 of nitrogen aboveground from the atmosphere (Peoples et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There are studies to identify potent indigenous and commercial Bradyrhizobia inoculants suitable for European conditions (Zimmer et al, 2016;Yuan et al, 2020) and attempt to incorporate soybeans in the no-till cover-crop system (Halwani et al, 2019). However, very little is known about the potential of soybeans in higher latitudes (Lamichhane et al, 2020;Schoving et al, 2020). Soybean seeds contain high nutrients for feed and food use, and the crop establishes nitrogen-fixing symbiosis with Bradyrhizobia, fixing 68% and 119 kg ha −1 of nitrogen aboveground from the atmosphere (Peoples et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Second, unlike crops such as sunflower or maize, soybean has a high degree of plasticity in vegetative traits and thus is capable of compensating seedling emergence losses due to its semi-determinate or indeterminate growth habit and ramification capacity ( Vega and Sadras, 2003 ; Andrade and Abbate, 2005 ). Indeed, the cultivar Isidor used in this study is characterized by semi-determinate growth while cultivars Ecudor and Santana are characterized by indeterminate growth ( Schoving et al, 2020 ). However, the rate of soybean emergence may significantly impact grain yield when a lower density than used herein is adopted and when cultivars with determinate growth habit is used ( Vega and Sadras, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we used from our database ( Lamichhane et al, 2020a ) the parameter values related to hypocotyl and radicle elongation, and seedling mortality rates under soil aggregates for the cultivars used in this study. In contrast, we estimated parameters of the model related to seed germination at different temperatures and water potentials of all three soybean cultivars used in this study that have contrasting characteristics ( Schoving et al, 2020 ): cv. Ecudor belongs to the maturity group II (MGII), is characterized by indeterminate growth, and has big round leaves; cv.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The infection of this pathogen is observed on all parts of the plant i.e., branches, leaves, pods, petioles, root, stem, and seeds on soybean ( Gupta et al, 2012 ), however, the key indications of disease are observed after the flowering stage in infected plants, i.e., R7 stage, especially in low humidity level and high-temperature conditions ( Schoving et al, 2020 ). Chlorosis of leaves, premature defoliation, and reduced vigor are the major symptoms observed in the infected plants ( Romero Luna et al, 2017 ), which result in reduced productivity, sterility of pod, and formation of crinkled and tiny seeds.…”
Section: Methodsmentioning
confidence: 99%